Kemuliaan dan Memuliakan - Muhith Muhith (STID DI AL-HIKMAH, 2015)
Human perception of itself will determine the attitude and temperament in this life. Good self-concept will help him to do good and vice versa. People who felt himself despised, insulted or humiliated will tend to humiliate himself and humiliate others. God has bestowed upon this man a variety of glory and excellence. Realize the advantages and the glory that God has bestowed it will be able to help the man keep his glory, to love goodness corresponding to his noble nature and away from vices that would demeaning.